Impact of Wheat on Soybean Cyst Nematode Population Density in Double-Cropping Soybean Production - Rocha, Leonardo F.; Pimentel, Mirian F.; Bailey, John; Wyciskalla, Terry; Davidson, Dan; Fakhoury, Ahmad M.; Bond, Jason P. (Frontiers in Plant Science, 2021)
Double cropping (DC) is defined as producing more than one crop on the same parcel of land in a single growing season. It is reported to have many benefits when incorporated in cropping systems, including improving soil health. In some DC systems, soybean is planted following winter wheat. Soybean cyst nematode (SCN) (Heterodera glycines Ichinohe) is a major soybean pathogen, and several reports suggest suppressive effects of wheat on SCN population densities. Field trials were conducted from 2017 to 2018 to investigate the effect of wheat on SCN populations in DC soybean. Nine fields with three levels of initial SCN populations (low, moderate, and high) were selected in Illinois. Wheat (WT) was planted in strips alternating with strips-maintained weed-free and under fallow (FL) over winter and early spring. Soybean was planted in all strips after wheat harvest. SCN egg densities were acquired at four timepoints: wheat establishment, post-wheat/pre-soybean, mid-soybean (R1) and post-soybean harvest. WT strips reduced SCN egg densities compared to FL strips at R1 stage (beginning of flowering) (-31.8%) and after soybean harvest (-32.7%). Soil physical and chemical changes, effects of wheat root exudates, and shifts in the soil microbial community are proposed as possible causes of reduced SCN populations where wheat precedes soybean. Double-cropping soybean with wheat has the potential to improve soil organic matter, suppress SCN, and it is a good system to provide additional farm income. This study is meant to be a first step towards a better understanding of the mechanisms that govern the suppression of SCN by wheat.